Effect of repetitive transcranial magnetic stimulation on patients with severe depression: a study protocol for systematic review and meta-analysis of randomised clinical trials - Hao Wu; Fang Han; Shuai Tao; Shanshan Liang; Danyang Li; Yutong Me; Hongyu Fan; Gaofeng Zhang (BMJ Open)
Introduction Depression is characterised by easy recurrence, high disability and high burden, and antidepressant therapy is the standard treatment. However, its treatment effect on patients with severe depressive disorder has been unsatisfactory. Previous studies have shown that repetitive transcranial magnetic stimulation (rTMS), as a neurotherapy, can effectively mitigate the severity of depressive symptoms. Yet, more evidence is still required for TMS to treat severe depression. This study will be the first systematic review of the efficacy and tolerability of TMS for treating severe depression. We expect it to guide future clinical practice of TMS for the treatment of psychiatric disorders.Methods and analysis We will search for the randomised controlled trial (RCT) involving rTMS for treating depression in eight electronic databases, including PubMed, Web of Science, EMBASE, the Cochrane Library and Wanfang Database, from publication up to September 2021. We will define Improvement in depressive symptoms, the difference between pretreatment (baseline) and post-treatment as the primary outcomes. The difference between pretreatment and post-treatment changes in resting state fMRI will be regarded as the secondary outcomes. Quality assessment of the included articles will be independently performed according to the Cochrane Risk of Bias tool.Ethics and dissemination Ethical approval is not essential because there is no need to collect individual patient data. And this study will be published in a peer-reviewed journal.Trial registration number CRD42020211460.